Meiotic configuration and rDNA distribution patterns in Six Rubus taxa - Chen, Qing; Wang, Yan; Nan, Hong; Zhang, Li; Tang, Haoru; Wang, Xiaorong (The Indian Journal of Genetics and Plant Breeding, 2016)
More than 200 Rubus species described so far have been included in subgenera Idaeobatus and Malachobatus. Tremendous amount of genetic diversity exists in Rubus due to inter- or intra-species hybridization, polyploidization, or agamospermy make it a typical taxonomically challenging but genetically intriguing genus among land plants. In present study, meiotic pairing behavior and the distribution patterns of 45S and 5S ribosomal DNA (rDNA) arrays were assessed by fluorescence in situ hybridization (FISH) in six Rubus taxa with ploidy ranging from diploid (2n=14) to octoploid (2n=56). At all ploidy levels, bivalent pairing is the most predominant form in meiotic configuration.Very few multivalents were observed in tetraploid or octoploid samples. FISH analysis revealed two 45S rDNA sites in each of the two diploid taxa. Each of the polyploids (2n=28) studied had the expected multiples of this number except the tetraploid R. setchuenensis (with only three sites). On the contrary, both diploid and tetraploid taxa had two 5S rDNA loci, while the octoploid R. buergeri carried only three sites. Both meiotic behavior observations and FISH results support that Rubus polyploids might be of allopolyploid in origin.